3D Poly(Lactic Acid) Scaffolds Promote Different Behaviors on Endothelial Progenitors and Adipose-Derived Stromal Cells in Comparison With Standard 2D Cultures - Biagini, Giuliana; Senegaglia, Alexandra Cristina; Pereira, Tarciso; Berti, Lucas Freitas; Marcon, Bruna Hilzendeger; Stimamiglio, Marco Augusto (Frontiers in Bioengineering and Biotechnology, 2021)
Tissue engineering is a branch of regenerative medicine, which comprises the combination of biomaterials, cells and other bioactive molecules to regenerate tissues. Biomaterial scaffolds act as substrate and as physical support for cells and they can also reproduce the extracellular matrix cues. Although tissue engineering applications in cellular therapy tend to focus on the use of specialized cells from particular tissues or stem cells, little attention has been paid to endothelial progenitors, an important cell type in tissue regeneration. We combined 3D printed poly(lactic acid) scaffolds comprising two different pore sizes with human adipose-derived stromal cells (hASCs) and expanded CD133+ cells to evaluate how these two cell types respond to the different architectures. hASCs represent an ideal source of cells for tissue engineering applications due to their low immunogenicity, paracrine activity and ability to differentiate. Expanded CD133+ cells were isolated from umbilical cord blood and represent a source of endothelial-like cells with angiogenic potential. Fluorescence microscopy and scanning electron microscopy showed that both cell types were able to adhere to the scaffolds and maintain their characteristic morphologies. The porous PLA scaffolds stimulated cell cycle progression of hASCs but led to an arrest in the G1 phase and reduced proliferation of expanded CD133+ cells. Also, while hASCs maintained their undifferentiated profile after seven days of culture on the scaffolds, expanded CD133+ cells presented a reduction of the von Willebrand factor (vWF), which affected the cells’ angiogenic potential. We did not observe changes in cell behavior for any of the parameters analyzed between the scaffolds with different pore sizes, but the 3D environment created by the scaffolds had different effects on the cell types tested. Unlike the extensively used mesenchymal stem cell types, the 3D PLA scaffolds led to opposite behaviors of the expanded CD133+ cells in terms of cytotoxicity, proliferation and immunophenotype. The results obtained reinforce the importance of studying how different cell types respond to 3D culture systems when considering the scaffold approach for tissue engineering.